Monitoring and Evaluation System for Subsidized Fertilizer Distribution (SIMETRI) - Eva Yulia Puspaningrum; Agung Mustika Rizki; Annisaa Sri Indrawanti; Firza Prima Adityawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2024)
Subsidized fertilizer distribution is a government policy to increase agricultural productivity in Indonesia. However, this distribution resulted in inequality and lack of supervision. This causes the distribution of fertilizers that are not on target and uncontrolled. So far, Food Security and Agriculture Department (FSAD) in Bojonegoro has experienced problems controlling the distribution of subsidized fertilizers. These obstacles are due to the unsynchronized data and the lack of extension workers to check directly on the location. Therefore, a monitoring and evaluation system is needed for the distribution of subsidized fertilizers. This system will integrate data from fertilizer distributors, subsidized farmers group, africultural instructor from sub-districts and the FSAD Bojonegoro can supervise fertilizer distribution. With a monitoring and evaluation system, Agricultural extension officer can monitor fertilizer stocks, thereby minimizing stock shortages and increasing efficiency in the distribution of subsidized fertilizers. And the FSAD can evaluate the distribution fertilizer in Bojonegoro District. The technique used for system development is SDLC (System Development Life Cycle) with Waterfall Model. This system has features such as User Account Verification by Administrator, fertilizer applications from farmer groups, validation of fertilizer by distributors, validation and reset of fertilizer stocks by agricultural instructur officer and evaluate of FSAD Bojonegoro. FSAD Bojonegoro can easily access information regarding the distribution of subsidized fertilizer and evaluate the distribution to performance improvement. System testing has been carried out and the results are that all system performance functions can run well according to their function.